Investment Analysis and Selection on Apple, Netflix, and Amazon - Li, Guiming (Transactions on Economics, Business and Management Research, 2024)
In the present economy, Apple, Netflix, and Amazon stand out as leaders in their perspective sector, such as technology, entertainment, and e-commerce. The study investigates firms using financial data from 2023 to 2024 sourced from professional online database. The analysis focuses on key financial metrics such as risk, profitability, and market ratios, providing comprehensive understanding of the investment feasibility. The finding emphasizes crucial contrasts in financial risk and returns potential while fitting the preferences of different types of investors. Value investors’ asset selection is all three firms due to Apple's strong market position, Netflix's lowest P/B ratio, Amazon's long-term growth potential, and the solid fundamentals of all companies. Income investors select Apple to invest in since Apple offers a dividend yield of 0.45%, though this yield is quite low, other companies have no dividends. PEG investors will avoid all three firms because the growth prospects of Apple, Amazon, and Netflix are already highly valued, limiting the potential for significant growth. Momentum investors may invest in Apple and Amazon due to their upward-moving averages. Smart money investors invest in Apple and Amazon, influenced by Warren Buffett's investments, and also consider Netflix due to Carl Icahn's involvement. Investors seeking insider buying will avoid all three companies as there has been no reported insider buying. Lastly, this study provides significant insights for investors, enabling them to align their stock selections with specific financial goals and risk appetites, eventually leading to more informed and strategic investment decisions to be made.